Single-cell DNA from West Greenland marine sediments suggests presence of Protoperidinium tricingulatum in the Arctic - Luostarinen, Tiia; Ribeiro, Sofia; Zimmermann, Heike H.; Kvorning, Anna B.; Heikkilä, Maija (Journal of Eukaryotic Microbiology, 2023)
Spiny brown dinoflagellate cysts are commonly used as sea-ice indicators in the Arctic, but their biological affinities are not well known. We present the first indication of hitherto temperate Protoperidinium tricingulatum in the Arctic based on single-cell LSU rDNA sequencing from sediments of the Disko Bay-Vaigat Sound, West Greenland. The morphological similarity of the sequenced cyst morphotype to the sea-ice indicator Islandinium? cezare morphotype 1 (Journal of Quaternary Science, 16, 2001 and 621) is striking. The morphology of the isolated cysts, as well as those observed in the total cyst assemblage following standard palynological preparation, both resemble either I.? cezare morphotype 1 or P. tricingulatum, suggesting that the specimens may in fact be close morphological variants of the same species. In addition, nine LSU rDNA sequences were obtained from morphological variants assigned to Islandinium minutum s.l.: including both subspecies minutum and subspecies barbatum. The two subspecies could not be differentiated based on partial LSU rDNA sequencing. Overall, Arctic spiny brown dinoflagellate cyst species may be morphologically more diverse and taxonomically more complex than shown earlier and further genetic and morphological studies are needed. Importantly, the value of cysts as palaeoecological indicators depends on a sound understanding of their biological affinity and taxonomy. Peer reviewed